Cell death induction by Ranunculus ternatus extract is independent of mitochondria and dependent on Caspase-7 - Fang, Ming (3 Biotech, 2020)
Ranunculus ternatus is a traditional Chinese medicine with an anticancer effect, but its underlying mechanism is unknown. In this study, we demonstrated by MTT assay that ethyl acetate extract (RTE) from R. ternatus exerts cytotoxic effects on human T cell lymphoma Jurkat cells. Then, to test the apoptosis induction ability of RTE to induce apoptosis, we analyzed phosphatidylserine exposure, DNA fragmentation, and caspase cleavage. RTE induced phosphatidylserine exposure and caspase-7 cleavage, but not caspase-3 cleavage. Sub-G1 cells were accumulated but DNA fragmentation was not observed. A pan-caspase inhibitor Z-Asp-CH(2)-DCB suppressed RTE-induced caspase cleavage and the above-described events. RTE also induced cell death in caspase-3 null human breast cancer MCF-7 cells, indicating that RTE-induced apoptotic-like cell death depends on the activation of one or more caspases, but not caspase-3. Moreover, RTE-induced cell death was not suppressed in Bcl-2 overexpressing Jurkat cells, suggesting that mitochondria were not involved in RTE-induced cell death. In conclusion, RTE-induced cell death was independent of mitochondria and dependent on caspase-7.